Molecular characterization of a bovine adenovirus type 7 (Bovine Atadenovirus F) strain isolated from a systemically infected calf in Germany - Sonja T. Jesse; Malgorzata Ciurkiewicz; Ute Siesenop; Ingo Spitzbarth; A. D. M. E. Osterhaus; Wolfgang Baumgärtner; Martin Ludlow (Virology Journal, 2022)
Abstract Bovine adenovirus 7 (BAdV-7) is an unclassified member of the genus Atadenovirus with a worldwide distribution and has been reported to induce clinical disease of varying severity in infected cattle, ranging from asymptomatic infections to severe enteric or respiratory disease. In this study, we used next-generation sequencing to obtain the first complete genome sequence of a European strain of BadV-7, from pooled spleen and liver tissue obtained from a deceased newborn Limousin calf. Histopathological analysis and electron microscopy showing systemic lesions in multiple organs with intranuclear amphophilic inclusions observed in endothelial cells in multiple peripheral tissues. Virus isolation was readily achieved from tissue homogenate using bovine esophagus cells (KOP-R), a strategy which should facilitate future in vitro or in vivo BAdV-7 studies. Phylogenetic analysis of available genome sequences of BAdV-7 showed that the newly identified strain groups most closely with a recent BAdV-7 strain, SD18-74, from the USA, confirming that this newly identified strain is a member of the Atadenovirus genus. The fiber gene was found to be highly conserved within BAdV-7 strains but was highly divergent in comparison to Ovine adenovirus 7 (OAdV-7) (39.56% aa sequence identity). Furthermore, we report a variable region of multiple tandem repeats between the coding regions of E4.1 and RH5 genes. In summary, the presented pathological and molecular characterization of this case suggests that further research into the worldwide molecular epidemiology and disease burden of BAdV-7 is warranted.